The Effect of Biofertilizer on the Incubation of Cattle Manure of Kailan (Brassica olearaceae) - Asyhad, Firmansyah Nur; Aisyah, Aisyah; Miska, Moh. Ega Elman; Saputry, Dinda Helma (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The production of kailan can be improved by maintaining soil fertility. This study aims to determine the effect of incubation duration and biofertilizer application, as well as the interaction between incubation duration and biofertilizer application, on the growth and yield of kailan plants. The study used a Completely Randomized Design (CRD) with two factors. The first factor was incubation duration with four treatment levels: no incubation (I0), 1-week incubation (I1), 2-week incubation (I2), and 3-week incubation (I3). The second factor was the application of biofertilizer at three concentration levels: no biofertilizer (D0), biofertilizer application at 15 ml/L (D1), and biofertilizer application at 30 ml/L (D2). The results showed that the incubation of cattle manure significantly affected the growth and yield of kailan plants. Cattle manure incubation affected plant height, number of leaves, stem diameter, leaf area, fresh plant weight, fresh shoot weight, dry shoot weight, fresh root weight, and dry root weight, especially during the 3-week incubation (I3). Biofertilizer application affected plant height, stem diameter, and fresh plant weight at concentrations of 15 ml/L (D1) and 30 ml/L (D2).